Studi Evaluatif Penyelenggara Pendidikan Agama Hindu Terhadap Pencapaian Pendidikan Agama Hindu Sekolah Menengah Atas Dwijendra Di Denpasar - I Nyoman Subagia; I Made Suta (Cetta: Jurnal Ilmu Pendidikan, 2020)
This research has several underlying factors, including; (1) to date there has been no independent or related evaluation carried out so that Hindu education in the Dwijendra school in Denpasar is unknown, (2) Interesting phenomena here are found in small islands in Indonesia, such as in Bali where the majority of the population is Hindu, and Hindu people prefer schools in non Hindu-based schools, it is suspected, school-based management in Dwijendra High School in Denpasar has not been maximally achieved in accordance with the goals of the organization. The main objective of this study is to determine the effectiveness of independent variables or predictors consisting of context variables (X1), input (X2), process (X3), and product (X4) while competency achievement is treated as a dependent variable or criterion with a symbol (Y). The analytical method in accordance with the objectives of the research design used is simple or multiple regression because it consists of three independent variables and one dependent variable. The results of the study are as follows: (1) there is a relationship between context and the achievement of Hindu religious education competencies with a value of 0.229 using a significance level of 0.05 (0.000 <0.05), then the alternative hypothesis is accepted, (2) there is a relationship between inputs with the achievement of Hindu religious education competence with a value of 0.180 using a significance level of 0.05 (0.000 <0.05), then the null hypothesis is accepted, (3) there is a relationship between the process of achieving Hindu religious education competence with a value of 0.957 using the level significance of 0.05 (0,000 <0.05), then the null hypothesis is accepted, (4) there is a relationship between the product and the achievement of Hindu religious education competence with a value of 0.339 using a significance level of 0.05 (0,000 <0.05), then the hypothesis zero accepted, (5) there is a relationship between the context, input, process, and product with the achievement of Hindu religious education competence with a value of 0.276, de using a significance level of 0.05 (0,000 <0.05).